THE USE OF ONLINE AUTHENTIC MATERIALS IN EFL INSTRUCTION: TEACHERS’ PERCEPTIONS AND CHALLENGES (SCIENCE TIME JOURNAL, 2026)
This study investigates the use of online authentic materials in English as a Foreign Language (EFL) teaching, focusing on the types of materials used, teachers’ perceptions, and challenges encountered during implementation. Findings indicate that teachers utilize a variety of online resources, including YouTube videos, podcasts, digital articles, news items, and web-based short stories. Teachers generally perceive online authentic materials as comparable to traditional materials, differing mainly in delivery format. They also emphasize the importance of adapting materials to align with learning objectives and students’ proficiency. Nevertheless, face-to-face instruction is often preferred due to fewer technical difficulties and easier classroom management. Key challenges include limited internet access, classroom management issues, and students’ variable language competence. The study highlights the potential of online authentic materials to enhance motivation, learner autonomy, and exposure to real-world language.